2024
DOI: 10.20517/jtgg.2023.36
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted nature of young-onset diabetes - can genomic medicine improve the precision of diagnosis and management?

Juliana CN. Chan,
Chow Elaine,
Alice Kong
et al.

Abstract: Young-onset type 2 diabetes (YOD), defined as diabetes diagnosis before age 40, has an aggressive clinical course with premature mortality, in part due to long disease duration and lack of evidence to guide diagnosis and management. Autoimmune type 1 diabetes, maturity-onset diabetes of the young (MODY), and latent autoimmune diabetes in adults (LADA) are subtypes of diabetes in young people, which, however, cannot fully explain their complex clinical course. Similarly, family members carrying the same rare ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…The art of genome sequencing and analysis offers valuable insights into early and precise diagnosis, personalised treatment and management of various diseases, highlighting the expanding influence of genomics across diverse areas of clinical practice. In this special issue, we gathered an application of genomics in prenatal molecular diagnosis of a rare disease, X-linked Bartter Syndrome, as well as reviews on how genomics benefits clinical practice in various common disease cohorts, such as inherited cardiovascular conditions (ICCs), adult myeloid leukaemia (AML), and young-onset diabetes (YOD) [7][8][9][10] . Xu et al presented an application of genomics in the prenatal diagnosis of Bartter syndrome (BS), which is important for the early onset of polyhydramnios related to BS [7] .…”
Section: (1) Integrating Genomic Medicine Into Clinical Carementioning
confidence: 99%
See 1 more Smart Citation
“…The art of genome sequencing and analysis offers valuable insights into early and precise diagnosis, personalised treatment and management of various diseases, highlighting the expanding influence of genomics across diverse areas of clinical practice. In this special issue, we gathered an application of genomics in prenatal molecular diagnosis of a rare disease, X-linked Bartter Syndrome, as well as reviews on how genomics benefits clinical practice in various common disease cohorts, such as inherited cardiovascular conditions (ICCs), adult myeloid leukaemia (AML), and young-onset diabetes (YOD) [7][8][9][10] . Xu et al presented an application of genomics in the prenatal diagnosis of Bartter syndrome (BS), which is important for the early onset of polyhydramnios related to BS [7] .…”
Section: (1) Integrating Genomic Medicine Into Clinical Carementioning
confidence: 99%
“…Their experience provides insights for international counterparts when implementing similar services in local healthcare centres to address the healthcare burden of ICCs. Leung et al reviewed that the genomic revolution in AML has ushered in a new era of personalised medicine, shifting the treatment paradigm from a generalised approach, which has reached an impasse, to one that targets individual genetic alterations [9] . The integration of genomics, the detection of measurable residual disease, drug sensitivity testing, and single-cell transcriptomics hold tremendous potential for optimising AML management through personalised approach based on genomic and transcriptomic information.…”
Section: (1) Integrating Genomic Medicine Into Clinical Carementioning
confidence: 99%
“…Collectively, these factors influence the age of onset of diabetes. 2 The long disease duration puts these young patients at high risk of poor quality of life, multiple morbidities, recurrent hospitalizations and premature mortality, which can be modified by control of risk factors, medications and self-management with ongoing support. [3][4][5][6] In contrast to declining trends of complications and death in older adults with T2D, population-level studies reported stagnation or even resurgence in incidence rates of cardiovascular disease and lower extremity amputation in patients with T2D in the youngest age group.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Despite this disproportionate burden in young patients with T2D, there is a lack of evidence-based practice guidelines in these patients who were under-represented in most clinical trials. 2 8 9 …”
Section: Introductionmentioning
confidence: 99%